Traumatic brain injury and post-injury sleep fragmentation differentially alter the microglial transcriptome - Taylor, Morgan A.; Boland, Rebecca; Houle, Samuel; Tapp, Zoe M.; Davis, Amara C.; Cotter, Christopher; Sheridan, John F.; Godbout, Jonathan; Kokiko-Cochran, Olga N. (Frontiers in Immunology, 2026)
IntroductionTraumatic brain injury (TBI) is a global source of injury-related death and disability, and survivors often suffer functional and psychiatric consequences that persist for years. Neuroinflammation, mediated in part by microglia, perpetuates chronic dysfunction after TBI and leaves survivors vulnerable to the effects of secondary immune challenges. Previous data from our lab shows that 30 days of mechanical sleep fragmentation (SF) aggravates microglia- associated neuroinflammation in C57BL/6 mice, impairing recovery after TBI. MethodsTo better understand the mechanisms through which microglia contribute to impairment following post-TBI SF, we used flow cytometry to analyze multiple cell types from brain and peripheral tissues of C57BL/6 mice who received a TBI or sham injury followed by 7 or 30 days of SF or control housing. Next, bulk RNA sequencing was used to analyze gene expression in microglia and coronal slice from the ipsilateral brain. We analyzed differentially expressed genes (DEGs) within each tissue type to determine how ipsilateral brain and microglia are independently influenced by TBI and SF. We also compared microglial DEGS directly to those of coronal slice, gaining novel insight into how microglia contribute to dysfunction in the ipsilateral brain after TBI and post-injury SF.ResultsFlow cytometry revealed transient increases in monocyte infiltration to the brain 7 days post-injury (DPI) that resolved by 30 DPI. SF did not exacerbate the immune response to injury within peripheral tissues or the brain at either of these time points. From our transcriptomic analysis, we identified distinct sets of DEGs which are uniquely dysregulated by TBI, SF, and the combination of TBI and SF. Notably, we found distinct subsets of olfactory genes that are differentially dysregulated by TBI and SF in the ipsilateral brain, as well as significant enrichment of cell-cell communication and steroidogenesis pathways that are specifically disrupted in microglia compared to the rest of the brain. DiscussionThrough in-depth transcriptional analysis we identify potential molecular targets that shed light on the mechanisms of TBI-induced microglial activity and reveal how SF after TBI alters this response. Together, these data could inform therapeutic strategies that target neuroinflammation to improve chronic recovery after brain injury.